THE TRANSLATION OF METAPHORS IN â€œEYES OF A BLUE DOGâ€ INTO â€œSEPASANG MATA ANJING BIRUâ€ - Rizaldi Sardani; Silvia Indriani (INOVISH JOURNAL, 2019)
This study aims at describing metaphors translated form English to Bahasa Indonesia in the short story entitled Sepasang Mata Anjing Biru that was translated from Eyes of a Blue Dog by Gabriel Garcia Marquez. It also aims at describing the translation strategies in translating the metaphors. This study applied descriptive qualitative research. The data of this study were all clauses that contained metaphors, and they were obtained from in the short story entitled Sepasang Mata Anjing Biru that was translated from Eyes of a Blue Dog. The data were collected by using observational method which was supported by note-taking techniques. The data analysis was conducted by using translational identity method, because English was used in this study. The results of analysis were presented by using an informal method. The results showed that in translating the metaphors, most of the metaphor in source language were translated into metaphors in target language, and only 1 metaphor were translated into simile.